TYPOLOGY OF COUNTRIES: DIFFERENT APPROACHES AND MODERN CLASSIFICATIONS - Amriyeva Shaxzoda Shuxratovna; Eshkuvatov Mirjahon Shaxzodovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The typology of countries has long been a subject of interest in the fields of economics, political science, and international relations. This article examines various approaches to classifying countries, ranging from traditional economic indicators like GDP and income levels to modern frameworks that incorporate political stability, governance quality, and human development metrics. It explores the evolution of country typologies, highlighting key methodologies such as the World Bank income classification, the Human Development Index (HDI), and more recent multidimensional approaches. By analyzing the strengths and limitations of these classifications, the article sheds light on their relevance in understanding global disparities, informing policy decisions, and addressing contemporary challenges such as sustainability and inequality.